The costs of bipolar disorder in the United Kingdom - Simon, J; Pari, AAA; Wolstenholme, J; Berger, M; Goodwin, GM; Geddes, JR (Wiley, 2021)
Objectives To estimate the individual cost and population-level economic burden of Bipolar Disorder (BD), and explore the impact of clinical and sociodemographic factors on costs in the United Kingdom.